O futuro do Estado no Brasil e seus impactos na sociedade: Quest\~oes para o desenvolvimento até 2035 - Raphael Camargo Lima; Maurício Pinheiro Fleury Curado (Instituto de Pesquisa Econômica Aplicada (IPEA), 2017)
– In Brazil, it has been difficult to elaborate governmental planning surpassing the four-year spectrum from the Pluriannual Plans. Despite the fact of long-term planning attracting a wide range of sectors, it still occupies a small space in both political and State agendas. Hence, the present study intends to initiate a new cycle of debates regarding the issue as it presents questions and factors to subsidy long-term strategies. Using methodological tools from Strategic Prospective, we present both the methodological approach to scenarios and the trends and uncertainties regarding the relationship between State and Society - contemplating topics such as organization of the state apparatus, governmental planning, federative relations and social participation. This study is part of Brazil 2035, a project whose objective is to provide subsidies to formulate long-term development strategies for Brazil through Prospective Scenarios. Thus, this text presents a preliminary stage of a prospective process regarding the identification and analysis of the main variables. We do not intend to be conclusive; but rather to present some key factors and questions, which will affect Brazilian development until 2035.
Keywords: C53; D73; L38; H10; H11; 330; strategic prospective; prospective scenarios; long-term planning; state; public management; public policy; federalism; social participation